2012
DOI: 10.2174/156720212803530645
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Intra-Nasal Erythropoietin Administration with Low Sialic Acid Content is without Toxicity or Erythropoietic Effects

Abstract: The objective of this investigation was to assess the toxicological potential of nasal formulation of erythropoietin with low sialic acid content (Neuro EPO) after 28 days of intra-nasal dosing in rats besides to evaluate the immunogenicity and erythropoietic effect of the test substance. Healthy Wistar rats of both sexes were used for 28 days subacute toxicity and immunogenicity assays. Doses evaluated were 3450, 4830 and 6900 UI/kg/day. The toxicological endpoints examined included animal body weight, food c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Lagarto et al (2012) observed a slight increase in Gl level within the normal range after 28 days of intra-nasal dosing of 6900 UI/kg/day Epo in healthy Wistar rats. Lee et al (2006) found that Gl and insulin concentrations were significantly lowered by the 25-day mountaineering activity where Epo increases, in male subjects group.…”
Section: Discussionmentioning
confidence: 75%
“…Lagarto et al (2012) observed a slight increase in Gl level within the normal range after 28 days of intra-nasal dosing of 6900 UI/kg/day Epo in healthy Wistar rats. Lee et al (2006) found that Gl and insulin concentrations were significantly lowered by the 25-day mountaineering activity where Epo increases, in male subjects group.…”
Section: Discussionmentioning
confidence: 75%